2012
DOI: 10.5961/jhes.2012.041
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Smoking Habit Among the Students and Faculty Members in Marmara University and Steady Cost of Smoking

Abstract: ÖzGeleceğin sağlık profesyonelleri olacak hekim, diş hekimi, eczacı, hemşire ve ebe adaylarının ve ilgili fakültelerdeki öğretim elemanlarının sigara içme alışkanlıkları ve nikotin bağımlılıklarının ölçülmesi, sigaranın öğrencilere ve öğretim elemanlarına durağan maliyetinin hesaplanması amaçlanmıştır. Çalışma kapsamına Marmara Üniversitesi Tıp, Diş Hekimliği, Eczacılık Fakülteleri ve Sağlık Bilimleri Fakültesi Hemşirelik-Ebelik Bölümü'ndeki öğrenciler ile öğretim elamanları dâhil edilmiştir. Veri toplama arac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…It was revealed that being older than 21 years, being in upper grades, and the presence of close friends who smoked increased the rate of smoking. Studies revealed that the frequency of smoking increases with increasing age [22,38]. In this study, a parallel increase was observed between the status of still smoking and age.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It was revealed that being older than 21 years, being in upper grades, and the presence of close friends who smoked increased the rate of smoking. Studies revealed that the frequency of smoking increases with increasing age [22,38]. In this study, a parallel increase was observed between the status of still smoking and age.…”
Section: Discussionsupporting
confidence: 76%
“…This rate was found to be 33% in the study of Azak [20], 30% in the study of Bedir et al [21], 22% in the study of Kaplanoğlu et al [22], and 18,7% in the study of Altay and Çetin [23]. Compared with these data, it can be said that the students in our study smoked less.…”
Section: Discussionsupporting
confidence: 43%
“…This is important in quitting smoking and in the emergence of serious health problems. The findings obtained demonstrate that there should be struggle against starting smoking at earlier ages [15]. In this context, becoming knowledgeable about young people's smoking addiction will increase the effects of health education activities.…”
Section: Introductionmentioning
confidence: 78%
“…In a study conducted in smoker students, Alikasifoglu et al reported that dependence levels varied by sex (20). In a study conducted in 2012, Kaptanoğlu et al detected a positive correlation between the level of dependence and age, and reported that the level of nicotine dependence increased as the age increased (30). This finding may suggest that the fight against this habit may become more challenging in older ages.…”
Section: Variables N (%)mentioning
confidence: 99%